Alzheimer’s disease and epilepsy: An increasingly recognized comorbidity - Yang, Fei; Chen, Liling; Yu, Yanying; Xu, Tingwan; Chen, Lu; Yang, Wenqian; Wu, Qian; Han, Yanbing (Frontiers in Aging Neuroscience, 2022)
Both Alzheimer’s disease (AD) and epilepsy are common chronic diseases in older people. Seizures and epileptiform discharges are very prevalent in AD and can occur since any stage of AD. Increasing evidence indicates that AD and epilepsy may be comorbid. Several factors may be related to the underlying mechanism of the comorbidity. Identifying seizures in patients with AD is a challenge because seizures are often clinically non-motor and may overlap with some AD symptoms. Not only seizures but also epileptiform discharges may exacerbate the cognitive decline in AD patients, highlighting the importance of early recognition and treatment. This review provides a comprehensive overview of seizures in AD from multiple aspects to provide more insight.